Multifunctional melamine-based multilayer foam with heterogeneous alternating structure towards electromagnetic interference shielding - Feng, Yujia; Liao, Huimin; Wang, Jian (Colloids and surfaces. A, Physicochemical and engineering aspects, 2023)
With the rapid development of 5G technology, there is an urgent need to endow electromagnetic interference (EMI) shielding materials multifunctionality to cope with various harsh environments. Herin, a multifunctional melamine-based EMI shielding composite with heterogeneous alternating multilayer structure were fabricated through the layer-by-layer stacking method, consisting of Ni coated melamine foam (MF@Ni) layers, Fe3O4@polydimethylsiloxane dipped MF layers (Fe3O4@PDMS/MF) and metallized polyimide fabric layer (PI@Ni). The synergistic electromagnetic loss and interfacial polarization loss formed by the selectively distributed conductive Ni coating and magnetic Fe3O4 nanoparticles result in a high EMI shielding effectiveness (SE) of 54.20 dB with an absorption (A) value of 0.51 for the multilayer MF-based composite. Moreover, since the micro/nano porous structure, the nonflammability of MF, the functional Ni coating and Fe3O4@PDMS filling, the multilayer foam owns thermal insulation and flame retardancy. This work provides a viable strategy for designing absorption-based EMI shielding materials with thermal insulation and flame retardancy, which accords with the next generation of multifunctional EMI shielding materials. [Display omitted] •Melamine-based composite combining multilayer structure with foam structure prepared by a simple and efficient method.•The EMI shielding effectiveness of the melamine-based composite could achieve 54.20 dB, and A value of 0.51.•The melamine-based composite owns good thermal insulation and flame retardancy.